Modern research methods in management - Linkova, Olena Yuriivna (National Technical University "Kharkiv Polytechnic Institute", 2026)
Management plays a key role in the effective operation of any business organization. Growing competition and economic instability create conditions in which the organization must constantly analyze its condition and assess the prospects of its activities. In this regard, the training of economic specialists with the skills of information search and critical thinking when choosing directions for solving applied problems of business organization plays an important role. Methodological guidelines for practical work on the academic discipline "Modern Research Methods in Management" are developed to assist in the study and organization of independent work of a PhD student. The presented material orients students to the study of primary sources and literature, which contains examples of practical application of the achievements of management science in the activities of domestic companies and companies operating in countries with a market economy. The methodological guidelines provide the structure of the academic discipline and topics for in-depth study. The purpose of teaching the discipline Modern Research Methods in Management: to familiarize PhD students with a multidimensional approach to conducting scientific research in the field of management. To provide students with knowledge about solving current management problems. The task of teaching the discipline: theoretical and practical training of PhD students on the issues of: organizational theories, management research methods, organizational process, analysis of the internal and external environment of organizations, the evolution of organizations, organizational effectiveness of research in management.
Keywords: methodological guidelines; research of management systems; organization as a society; evolution of management; special research methods in management